2020
DOI: 10.14710/ijred.2021.33118
|View full text |Cite
|
Sign up to set email alerts
|

The CO2/CH4 Separation Potential of ZIF-8/Polysulfone Mixed Matrix Membranes at Elevated Particle Loading for Biogas Upgradation Process

Abstract: Biogas is a renewable energy that has been explored widely in Indonesia to substitute non-renewable energy. However, the presence of certain gas, such as carbon dioxide (CO2), can decrease the calorific value and generate greenhouse gas. Hence, the separation of CO2 from methane (CH4) occurs as a crucial step to improve the utilization of biogas. The separation of CH4/CO2 can be conducted using a polymeric membrane that needs no chemical, hence considered as an environmentally friendly technique. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…With increasing ZIF‐8 loadings in PSF, the separation performance of CO 2 and CH 4 was gradually increased towards the 1991 upper bound. Compared to the other ZIF8/PSF based MMMs reported in the recent literature, 26‐29 membranes fabricated in this work still demonstrated higher CO 2 /CH 4 gas pair selectivity and CO 2 gas permeability. The 1.0 wt% ZIF‐8/PSF MMM fabricated in this work exhibits the highest CO 2 permeability and CO 2 /CH 4 ideal selectivity in comparison with the results obtained for the PSF based MMMs reported in the literature 64‐66 .…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…With increasing ZIF‐8 loadings in PSF, the separation performance of CO 2 and CH 4 was gradually increased towards the 1991 upper bound. Compared to the other ZIF8/PSF based MMMs reported in the recent literature, 26‐29 membranes fabricated in this work still demonstrated higher CO 2 /CH 4 gas pair selectivity and CO 2 gas permeability. The 1.0 wt% ZIF‐8/PSF MMM fabricated in this work exhibits the highest CO 2 permeability and CO 2 /CH 4 ideal selectivity in comparison with the results obtained for the PSF based MMMs reported in the literature 64‐66 .…”
Section: Resultsmentioning
confidence: 55%
“…They reported that MMMs incorporated with 30 wt% of ZIF‐8 demonstrated a 136% enhancement in CO 2 permeability and the CO 2 plasticization pressure was enhanced up to 25 bar. Sutrisna et al 26 . reported the performance of PSF based mixed matrix membranes for CO 2 /CH 4 separation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of modified ZIF‐8 MMM, the selectivity has increased 155% due to increased CO 2 permeability. Ideally, the incorporation of filler should also increase CO 2 /CH 4 selectivity because of the molecular sieving effect of ZIF‐8 (pore aperture size of 3.4 A°, CO 2 , and CH 4 of 3.3 and 3.8 A° respectively) but due to the complete frigid saturation and due to the limited flexibility, ZIF‐8 absorbs gasses of kinetic diameter which are relatively close, which reduces the selectivity of CO 2 /CH 4 of the MMMs as observed at 15 wt% of ZIF‐8 44 . Additionally, the presence of large agglomerates of ZIF‐8 particles as observed in FESEM images (Figure 4c,e), could also contribute in the reduction of selectivity 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, the incorporation of filler should also increase CO 2 /CH 4 selectivity because of the molecular sieving effect of ZIF-8 (pore aperture size of 3.4 A , CO 2 , and CH 4 of 3.3 and 3.8 A respectively) but due to the complete frigid saturation and due to the limited flexibility, ZIF-8 absorbs gasses of kinetic diameter which are relatively close, which reduces the selectivity of CO 2 /CH 4 of the MMMs as observed at 15 wt% of ZIF-8. 44 Additionally, the presence of large agglomerates of ZIF-8 particles as observed in FESEM images (Figure 4c,e), could also contribute in the reduction of selectivity. 45 On the other hand, the selectivity of NH 2 -ZIF-8 MMM has trend of increasing without any decrease which is due to the NH 2 group attraction toward CO 2 gas species and also, no large agglomerates of modified ZIF-8 particles were observed in MMMs FESEM images.…”
Section: Mixed Gas Permeation Testsmentioning
confidence: 94%
“…The addition of different MOFs, such as MIL-101(Cr) [31], Bio-MOF-1 [32], Cu 3 (BTC) 2 [33], and MIL-53(Al) [34], was shown to produce a beneficial effect in terms of gas permeabilities and selectivities. Different groups studied and reported the positive effect of ZIF-8 addition into Polysulfone hollow fibers, flat asymmetric or dense membranes [35][36][37][38][39][40][41][42]. However, most studies refer to a narrow set of analyzed gases, filler loadings, and test temperatures.…”
Section: Introductionmentioning
confidence: 99%